Downstream activities after laboratory testing in primary care: an exploratory outcome of the ELMO cluster randomised trial (Electronic Laboratory Medicine Ordering with evidence-based order sets in primary care). Issue 4 (4th April 2022) - Piessens, Veerle; Delvaux, Nicolas; Heytens, Stefan; Aertgeerts, Bert; De Sutter, An
Abstract : Objective: To estimate the rate and type of downstream activities (DAs) after laboratory testing in primary care, with a specific focus on check-up laboratory panels, and to explore the effect of a clinical decision support system (CDSS) for laboratory ordering on these DAs. Design: Cluster randomised clinical trial. Setting: 72 primary care practices in Belgium, with 272 general practitioners (GPs), randomly assigned to the intervention arm or the control arm. Participants: The study included 10 270 lab panels from 9683 primary care patients (women 55.1%, mean age 56.5). All adult patients who consulted one of the participating GPs during the trial period and needed a laboratory exam were eligible for participation. Interventions: GPs in the intervention group used a CDSS integrated into their online laboratory ordering system, while GPs in the control arm used their lab ordering system as usual. The trial duration was 6 months, with another 6 months follow-up. Main outcome measures: This publication reports on the exploratory outcome of DAs after an initial laboratory exam and the effect of the CDSS on these DAs. Results: 19.7% of all laboratory panels resulted in further diagnostic procedures (95% CI 18.9% to 20.5%) and 19% (95% CI 18.2% to 19.7%) in treatment changes. Check-up laboratory exams showed similar rates of DAs, with 17.5% (95% CI 13.8% to 21.2%) diagnostic DAs and 18.9% (95% CI 13.9% to 23.9%) treatment changes. Using the CDSS resulted in a significant reduction in downstream referrals (−2.4%; 95% CI −4.2% to −0.6%; p=0008), imaging and endoscopies (−0.9%; 95% CI −1.6% to −0.1%; p=0026) and treatment changes (−5.4%; 95% CI −9.5% to −1.2%; p=0.01). Conclusion: This is the largest study so far to examine DAs after laboratory testing. It shows that almost one in three laboratory exams leads to further DAs, even in check-up panels. Using a CDSS for laboratory orders may reduce the rate of some DAs. Trial registration number: NCT02950142 .